High Contrast Detection of Water‐Filled Terahertz Nanotrenches. Issue 21 (29th August 2018) - Jeong, Jeeyoon; Yun, Hyeong Seok; Kim, Dasom; Lee, Kang Sup; Choi, Han‐Kyu; Kim, Zee Hwan; Lee, Sang Woon; Kim, Dai‐Sik
Abstract: The convergence of nano‐optics with an aqueous environment is promising for future chemical or biological applications. While the rapid development in nanofabrication has led to the realization of sub‐10 nm nanogaps of various structures, coupling water into high aspect ratio metallic nanogaps with a well‐defined area is not yet demonstrated. Here, arrays of 10 nm wide metallic trenches are reported filled with dielectric, air, liquid water, and various molecules in optical hotspots. Due to the high height‐to‐width aspect ratio of 20:1 and strong gap plasmon coupling in the 10 nm width, the trenches show distinct spectral changes at terahertz frequencies under changing gap materials, from which the full etching and water filling of the 10 nm gap can be unambiguously confirmed. A 75% transmitted amplitude decrease is observed through 200 nm deep trenches upon water filling, which converts to an effective 1100‐fold increase in the water absorption coefficient. The gap‐filling scheme can be applied to distinguish different liquids with 400 attoliters of volume or to detect rhodamine 6G molecules inside the gap with surface‐enhanced Raman scattering. Accordingly, the scheme can also be applied to a general class of polar organic molecules suitable for various biological or chemical applications. Abstract : Arrays of 10 nm wide metallic trenches filled with water, air, dielectrics and various molecules are reported. High aspect ratio of the trenches leads to distinct spectral changes at terahertz frequencies upon changes in gap materials. The trenches can be used to distinguish different liquids with 400 attoliters of volume and are also capable of detecting macromolecules.